(untitled) (Journal of Contemporary Educational Policies and Practices, 2022)
This study aims to identify the characteristics of Vietnamese teachers’ classroom observations. The analysis was conducted using data from the ten teachers who struggled to introduce the new curriculum during the 2000s. The analysis applied from the literature on the teachers’ video reflection revealed that those who participated in weekly sessions of Lesson Study for Learning Community (LSLC) tended to identify students’ knowledge formation better than those who did not participate in the lesson study. The second qualitative analysis, focusing on effective and attitudinal aspects in observation, indicated that the teachers in LSLC schools could accept and respond to the classroom event by positing themselves in the seat of actors. The discussion is devoted to the application of the concept of middle voice to the LSLC teachers’ observation, to examine a possible extension of the literature which mainly relies on teachers’ active cognitive processes.